Infections Caused by Actinomyces neuii: A Case Series and Review of an Unusual Bacterium - Nathan Zelyas; Susan Gee; Barb Nilsson; Tracy Bennett; Robert Rennie (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Actinomyces neuii is a Gram-positive bacillus rarely implicated in human infections. However, its occurrence is being increasingly recognized with the use of improved identification systems. Objective. To analyse A. neuii infections in Alberta, Canada, and review the literature regarding this unusual pathogen. Methods. Cases of A. neuii were identified in 2013-2014 in Alberta. Samples were cultured aerobically and anaerobically. A predominant catalase positive Gram-positive coryneform bacillus with no branching was isolated in each case. Testing was initially done with API-CORYNE® (bioMérieux) and isolates were sent to the Provincial Laboratory for Public Health for further testing. Isolates’ identities were confirmed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry microbial identification system (MALDI-TOF MS MIS; bioMérieux) and/or DNA sequencing. Results. Six cases of A. neuii infection were identified. All patients had soft tissue infections; typically, incision and drainage were done followed by a course of antibiotics. Agents used included cephalexin, ertapenem, ciprofloxacin, and clindamycin. All had favourable outcomes. Conclusions. While A. neuii is infrequently recognized, it can cause a diverse array of infections. Increased use of MALDI-TOF MS MIS is leading to increased detection; thus, understanding the pathogenicity of this bacterium and its typical susceptibility profile will aid clinical decision-making.